The little ghost who was a quilt - Nason, Riel, 1969- (Tundra Books, 2020)
"Ghosts are supposed to be sheets, light as air and able to whirl and twirl and float and soar. But the little ghost who is a quilt can't whirl or twirl at all, and when he flies, he gets very hot. He doesn't know why he's a quilt. His parents are both sheets, and so are all of his friends. (His great-grandmother was a lace curtain, but that doesn't really help cheer him up.) He feels sad and left out when his friends are zooming around and he can't keep up. But one Halloween, everything changes. The little ghost who was a quilt has an experience that no other ghost could have, an experience that only happens because he's a quilt... and he realizes that it's OK to be different."--